2018
DOI: 10.11646/zootaxa.4442.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Lyrodus mersinensis sp. nov. (Bivalvia: Teredinidae) another cryptic species in the Lyrodus pedicellatus (Quatrefages, 1849) complex

Abstract: New data from barcode index numbers (BINs) and 28S rRNA gene sequences confirm a cryptic species pair in Lyrodus pedicellatus from the eastern Mediterranean and European Atlantic coasts. Therefore, it is paramount to associate the new species to a scientific name for a reliable reference system of biological information. To this end, we describe Lyrodus mersinensis sp. nov., another cryptic species in the L. pedicellatus complex, and redescribe the `true´ L. pedicellatus. Both the description and redescription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 542 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…In the case of new species in cryptic complexes, the multilocus approach has been favoured to provide more information and stability in the species descriptions (Neusser et al, 2011; Jörger et al, 2012; Borges & Merckelbach, 2018; Trevisan et al, 2020). The multilocus approach will also address the well‐known fact that gene trees are not necessarily identical to species trees, for instance because of incomplete lineage sorting or horizontal gene transfer (Jörger & Schrödl, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of new species in cryptic complexes, the multilocus approach has been favoured to provide more information and stability in the species descriptions (Neusser et al, 2011; Jörger et al, 2012; Borges & Merckelbach, 2018; Trevisan et al, 2020). The multilocus approach will also address the well‐known fact that gene trees are not necessarily identical to species trees, for instance because of incomplete lineage sorting or horizontal gene transfer (Jörger & Schrödl, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we present fastachar , a software package designed to extract MDCs from one or several taxonomically informative DNA markers of a selected taxon compared with those of other taxa in a single step. The software was developed to determine MDCs for the description of Lyrodus mersinensis (Borges & Merckelbach, 2018) because none of the existing software packages met our needs.…”
Section: Introductionmentioning
confidence: 99%
“…Occurrence of multiple and highly divergent intraspecific lineages have been abundantly and increasingly reported in diverse groups of marine invertebrates, suggesting the existence of considerable hidden diversity (e.g. Nygren and Pleijel 2011, Lobo et al 2017, Nygren et al 2018, Borges and Merckelbach 2018. Several studies employed additional markers, mitochondrial and nuclear, essentially confirming the patterns observed with the DNA barcodes (e.g.…”
Section: Discussionmentioning
confidence: 63%
“…Recently, it has been suggested that teredinid diversity may be greater than previously thought (Huber, 2015; Shipway et al, 2016). This view is supported by the recent description of one new genus and several new species of teredinid bivalves (Macintosh, 2012; Borges & Merckelbach, 2018; Velásquez & Shipway, 2018). In addition, further reports suggest several more species (Shipway et al, 2016; Treneman et al, 2018) and at least one more genus (Lozouet & Plaziat, 2008) remain to be described.…”
Section: Discussionmentioning
confidence: 77%
“…These pallets, which are unique to Teredinidae, serve as watertight and predator-resistant plugs to seal the burrow entrance (Nair, 1966; Turner, 1966; Voight, 2015). Currently, there are 16 accepted genera composed of 70 species in the Teredinidae (Bulatov, 1933; Turner, 1966; Macintosh, 2012; Borges & Merckelbach, 2018; Velásquez & Shipway, 2018). However, it has been recently suggested that between 80-100 species likely exist (Huber, 2015; Shipway et al, 2016).…”
Section: Introductionmentioning
confidence: 99%